Digital Forensic and Tomography: A Decade of Insights - Sari, Rizqi Puspita; Phahlevy, Rifqi Ridlo; Fiddina, Irta (Proceedings of The ICECRS, 2023)
This dataset was acquired through a systematic search on the lens.org website, utilizing keywords "Digital forensic" and "tomography." The goal of this data collection is to facilitate future research in digital forensics with a specific focus on the intersection of digital forensic analysis and tomographic techniques. By applying filters to the data, including a range from 2002 to 2012, the selection of document type "journal articles," and subject matter "Law," we obtained a comprehensive dataset. The dataset contains 206 journal articles, making it valuable for researchers interested in exploring the legal aspects of digital forensics in conjunction with tomography. Notably, this dataset spans a decade, providing insights into the evolution of this field. It can serve as a rich resource for scholars and practitioners in the realms of both digital forensics and medical imaging, enabling further analysis, experimentation, and in-depth research. Highlight: Interdisciplinary Insight: This dataset combines digital forensics and tomography, offering interdisciplinary insights into their convergence over a decade. Legal Relevance: The dataset's focus on "Law" as the subject matter makes it a valuable resource for legal scholars and practitioners. Temporal Scope: Spanning from 2002 to 2012, this dataset reflects changes and advancements in digital forensics and tomography during this crucial timeframe. Keywords: Digital Forensic, Tomography, Legal Aspects, Dataset, Decade